AKIBAT PERJANJIAN HUKUM ANAK DIBAWAH UMUR DALAM PERJANJIAN BANGUN BAGI ATAS AKTA NOTARIS (Studi Putusan Perkara Perdata Nomor 07/Pdt.G/2010/PN-Kis Tentang Perjanjian Bangun Bagi) - KURNIASIH BR BANGUN (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Hasim Purba, SH, MHum2. Prof. Dr. Budiman Ginting, SH, MHum3. Prof. Dr. Muhammad Yamin, SH, MS,CN Capacity is one of the legal terms of an agreement. One of the elements of capacity in laws on agreement is age eligibility. Age limitation has caused legal uncertainty because it is regulated differently in some laws and regulations. An agreement is valid when all parties are 21 years old and/or married. Therefore, the panel of judges in Kisaran District Court that verify, hear and decide, pronounce the ruling for the civil case no. 07/Pdt.G/2010/PN-Kis on construction sharing agreement between Jamiluddin S and Segar as the Director of CV. Putra Mandiri grounded on the argument that Jamiluddin S was not capable of taking legal actions because he was not 21 years old yet when making the agreement. The research problems are how the validity of a legal action in a construction sharing agreemnt is, if it is taken by a minor, how about the consequences of a minor legal action in a construction sharing agreement for a notarial deed, and how the case of the construction sharing agreement made by a minor before a notary is settled by Kisaran District Court. Keywords: Consequences of a Minor's Legal Action, Construction Sharing Agreement, Notarial Deed